MRI evaluation of anterolateral ligament of the knee: a cross-sectional study in Malaysia - Ren, Yi Kow; Low, Chooi Leng; Siron @ Baharom, Khairul Nizam; Sheikh Said, Siti Nor Badriati (Cureus, Inc., 2021)
Introduction